Novel materials for CO2 adsorption and reduction to methanol via hydrogenation - Ezeh, Collins Izuchukwu (2018)
Sorption-enhanced catalysts are highly favored to improve the synthesis of methanol by hydrogenation process. This requires the development of selective catalysts and CO2 adsorbents that are sufficiently stable to tolerate cyclic regeneration during operation. The present work focuses on the assessment of the adsorption performance of novel layered double hydroxides acting as supports for copper based catalysts in the reduction of CO2 to methanol. Emphasis is placed on the stability and capacity of hybrids prepared using various preparation routes in order to optimize the CO2 uptake and conversion to methanol per mass of the catalyst. This parameter is crucial in the industrial implementation of the technology as it dictates the size of the adsorption units and reactors required. The co-precipitation of Cu2+, Zn2+ and Zr4+ species onto well-dispersed layered double hydroxides is shown to be an effective preparation method that ensures adequate interaction between the catalysts and the support. Prior to the synthesis of the material, individual enhancement of the catalyst and the LDH template were carried out respectively. The catalysts were prepared via various facile methods. Calcination of the catalysts facilitated the mixture of the Cu catalyst with the respective support bolstering the formation of intermolecular oxo-bridges which resulted to the thermal stability of the catalysts. The thermal performance of the catalysts was directly related to the increase in calcination temperature. However, this temperature was capped at 673K beyond which denaturing of the catalyst occurs. For all given preparation method, comparing the different catalysts based on the Cu-loading, the performance trend is as follows: CP>DP>IM. Other factors experimented to affect the thermal properties of the catalysts include the Cu-loading and heating rate. To improve CO2 adsorption, amine modified Layered double hydroxide (LDHs) were prepared via the conventional, ultrasonic and hydrothermal routes, followed by MEA extraction. A comparative study was conducted with consideration of the effect of functionalization route on the adsorption capacity, regeneration and lifetime of the adsorbent. It is revealed that increase in amount of SDS has an adverse effect on the CO2 adsorption performance by protonating considerable amount of active amino groups. This performance trend was observed across all experimented temperature with the CO2 adsorption capacity decreasing with increase in temperature. After amine modification, adsorption capacity increased by ca. 75-90% and ca.10-30% at 55 oC and 80 oC, respectively. However, by sonochemical modification, the adsorption capacity showed an increase from 12-108% depending on sonic intensity. This is attributed to the enhanced deprotonation of activated amino functional groups via the sonochemical process. Subsequently, this improved the effective amine efficiency by 60% of the conventional. In addition, the sonochemical process improved the thermal stability of the adsorbent as well as reducing the irreversible CO2 uptake, CUirrev, from 0.18 mmol/g to 0.03 mmol/g; hence improving the lifetime and ease of regenerating the adsorbent. This is presented by subjecting the prepared adsorbents to series of thermal swing adsorption (TSA) cycles until its adsorption capacity goes below 60% of the original CO2 uptake. While the conventional adsorbent underwent a 10 TSA cycles before breaking down, the sonochemically functionalized LDH went further than 30 TSA cycles. However, adsorbents prepared via hydrothermal route showed a better CO2 uptake capacity than sonochemical and conventional adsorbents. This is attributed to the decrease in weak basic sites (OH- groups) and moderate basic sites (M-O) and subsequent increase in number of strong basic sites (O2-). Therefore, the sonochemical-assisted hydrothermal treatment promoted the adsorption capacity of the adsorbent. However, the cyclic adsorption efficiency of the hydrothermally prepared sample was lowest ca. 53% compared to 76% and 60% for the sonochemical and conventional process respectively. Adopting the obtained factors for optimum synthesis and operation of both CuO/ZnO/ZrO2 catalyst and Mg-Al LDH adsorbent, a composite catalyst consisting of CuO/ZnO/ZrO2 catalyst on LDH template was synthesised and analysed for CO2 uptake capacity and catalytic activity with variation in Al3+ and Zr4+ compositions. The deposition of the catalyst on the LDH support was found not to alter significantly the CO2 uptake of the hydrotalcites but helps to maintain the surface heterogeneity. Characterization tests shows an improvement in structural modification. However, this is subject to the proportion of the considered varied metals. In addition, despite the high thermal stability of Zr4+, the composite material was observed to weaken in stability with increase in Zr4+ content. Nonetheless, the CO2 uptake capacity was observed to increase. A thorough kinetic analysis demonstrates that the adsorption mechanism is attributed to the chemical nature of the metals which promoted chemisorption as the dominating adsorption mechanism with little contribution from physisorption. CO2 conversion and methanol yield were also dependent on the nature and composition of the cations as well as the operating temperature. Al3+:(Al3++Zr4+) ratio of 0.4 was obtained as the best cation mix to attain maximum methanol yield. A preliminary catalyst screening shows that Cu/ZnO/ZrO2/Mg-Al LDH is a promising candidate to catalyze simultaneous adsorption and reduction of CO2 for methanol synthesis.